The Role of Non-pharmacological Treatments of Irritable Bowel Syndrome: A Literature Review - Mentel, Oliwia Wiktoria; Łabuda, Mikołaj; Bogucka , Adrianna; Sowińska , Teresa; Szema, Agnieszka; Sikora , Jakub; Słojewska , Aleksandra; Knychalska , Karolina; Kotkowiak , Agata; Królikowska , Klaudia (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Irritable bowel syndrome (IBS) is among the most frequently diagnosed gastrointestinal disorders posing a substantial burden on healthcare systems and presenting ongoing clinical challenges. IBS significantly affects quality of life because it is usually associated with chronic abdominal pain and altered bowel habits. Therapeutic approaches encompass both pharmacological and non-pharmacological strategies. Given the incomplete understanding of its pathophysiology, first-line treatment should prioritize non-pharmacological interventions, which are devoid of adverse effects. This article aims to give you an overview of the trials that have looked at the effects of non-pharmacological management of irritable bowel syndrome and to discuss their role in the treatment of IBS. Brief description of the state of knowledge: The group of most important non-pharmacological interventions in IBS treatment includes dietary modifications, particularly the low-FODMAP diet, as well as psychological therapies, including cognitive behavioral therapy, gut-directed hypnosis, and mindfulness-based interventions. Data from meta-analyses and randomized controlled trials (RCTs) highlight their efficacy in symptom reduction and quality of life improvement. A key consideration is the potential synergy between dietary and psychological approaches, as supported by emerging evidence. Conclusion: Low-FODMAP diet and psychological interventions, including cognitive behavioral therapy, gut-directed hypnosis, and mindfulness, are effective treatment strategies for irritable bowel syndrome. The analyzed studies, including meta-analyses and randomized controlled trials, confirm their significant impact on symptom reduction and improvement in patients’ quality of life. Given the incomplete understanding of IBS pathophysiology, non-pharmacological approaches should be considered first-line treatments, as they minimize the risk of adverse effects.